Population Dynamics of Aphid and its Bio-Control Agents in Wheat Crop - Ullah, Shifa; Bibi, Rehana; Bashir, Muhammad Amjad; Ibrahim, Muhammad; Saeed, Shafqat; Hussain, Muhammad Arshad (Pakistan Journal of Nutrition, 2014)
Aphid is a serious pest of wheat and other field crops. It is widely distributed in southern Punjab as well as other areas of the country. There are number of aphid species which are going to become pest of wheat crop. Experiment was conducted at farmer’s field in southern Punjab for population dynamics, number of aphid and bio-control agents (predator) recorded on weekly using diagonal method by randomly selecting 30 plants from each fields. Aphid attack started in 1st week of January in all plots and increased with the vegetative growth of plant and reached at peak level in the 3rd week of March and after that its population started to decrease and population of bio-control agents was low at start but maximum during the March when aphid population was at its peak level.